PENGARUH KECERDASAN INTELEKTUAL, KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL TERHADAP PERILAKU ETIS PROFESI AUDITOR DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MODERASI (STUDI EMPIRIS PADA BPKP PERWAKILAN PROVINSI JAWA TENGAH) - Arti Setiyani, 13.05.52.0245; Jaeni, Jaeni (Students' Journal of Accounting and Banking, 2017)
This study examines the effect of intellectual intelligence, emotional intelligence, spiritual intelligence on auditor behavior with locus of control as a moderation variable. Respondents in this study are the auditors in BPKP Central Java Province. The number of auditors who menjadisampelpenelitiadalah 81 of 170 auditors registered in BPKP Central Java. Method of determining the sample used is to use convenience sampling, while the method of data processing used research is analysis multiple regression and moderated reggresion moderated (MRA). The results showed that intellectual intelligence has no effect on ethical behavior, emotional intelligence has positive effect on ethical behavior, spiritual intelligence has positive effect on ethical behavior, locus of control has positive effect on ethical behavior, and locus of control bias moderate intellectual intelligence relation, emotional intelligence, spiritual intelligence to the auditor's ethical behavior Keywords: intellectual intelligence, emotional intelligence, spiritual intelligence, ethical behavior, locus of control